Comparative Study of Oxidative Stress Markers, Clinical Chemistry Indicators, and Neurological Biomarkers Implicated in Disease Progression in Progressive and Stable Vitiligo - Muhammad Imran Khan, Zartaj Liaqat, Saleha Akram Nizami, Ghulam Mustafa Mahmood, Aisha Malik, Mariya Ali (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Vitiligo progression is thought to reflect a convergence of redox imbalance, metabolicsusceptibility, and neuro-immune dysregulation. This prospective comparative study enrolled 180adults with nonsegmental vitiligo, stratified at baseline